Modelling of Pulsed Electric Field (PEF) Pretreatment on Fresh Moringa oleifera Leaves Extraction Using Response Surface Methodology (RSM) - Sukardi, Sukardi; Pranowo, Dodyk; Safitri, Puput (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2022)
AbstractMoringa leaves are a source of high antioxidants. This study aims to find an equation model for the extraction conditions of Moringa leaves with Pulsed Electric Field (PEF) pretreatment. Fresh Moringa leaves were treated with PEF in various voltages (1,000, 1,500, and 2,000 Volts), frequency (1,000, 1,500 and 2,000 Hz) and extraction time (4, 5 and 6 hours) as the factors studied. The best results and mathematical equation models obtained were determined from the extraction process. The parameters observed were yield, total phenolic compounds, and antioxidant activity. The Response Surface Method (RSM) was chosen to determine the equation model for the voltage, frequency, and extraction time combination. The results of ANOVA (Sum of Squares, Lack of Fit, and p-value) show that the model is adequate to present experimental data. The analysis results showed a significant value for total phenol in a quadratic equation, extract yields in a linear equation, and antioxidant activity in a linear equation. The model is presented in a 2-D contour graph and a 3-D response surface. The equation model shows that the best treatment is a PEF voltage of 2,000 Volts, frequency of 1,000 Hz, and extraction time of 4 hours.Keywords: antioxidant, equation model, moringa leaf, Pulsed Electric Field, Response Surface Method AbstrakDaun kelor merupakan salah satu sumber antioksidan yang tinggi. Penelitian ini bertujuan untuk mencari model persamaan kondisi ekstraksi daun kelor dengan perlakuan pendahuluan Pulsed Electric Field (PEF). Daun kelor segar diperlakukan dengan PEF dalam berbagai tegangan (1.000, 1.500, dan 2.000 Volt), frekuensi (1.000, 1.500 dan 2.000 Hz) dan waktu ekstraksi (4, 5 dan 6 jam) sebagai faktor yang diteliti. Hasil terbaik dan model persamaan matematika ditentukan dari proses ekstraksi. Parameter yang diamati adalah rendemen, total senyawa fenol, dan aktivitas antioksidan. Response Surface Method (RSM) dipilih untuk mengetahui model persamaan kombinasi tegangan, frekuensi, dan waktu ekstraksi. Hasil ANOVA (Sum of Squares, Lack of Fit, dan p-value) menunjukkan bahwa model layak untuk menyajikan data eksperimen. Hasil analisis menunjukkan nilai yang signifikan pada total fenol dalam persamaan kuadratik, hasil ekstrak dalam persamaan linier, dan aktivitas antioksidan dalam persamaan linier. Model dipresentasikan dalam grafik kontur 2-D dan permukaan respons 3-D. Model persamaan menunjukkan bahwa perlakuan terbaik adalah tegangan PEF 2.000 Volt, frekuensi 1.000 Hz dan waktu ekstraksi 4 jam.Kata kunci: antioksidan, daun kelor, model persamaan, Pulsed Electric Field, Response Surface Method